Event-related potentials in Japanese childhood chronic fatigue syndrome - Tomoda, Akemi; Mizuno, Kei; Murayama, Nobuki; Joudoi, Takako; Igasaki, Tomohiko; Miyazaki, Makoto; Miike, Teruhisa (Journal of Pediatric Neurology, 2007)
The aim of this study was to investigate cognitive functions such as allocation and information processing in patients with childhood type chronic fatigue syndrome (CCFS) using event-related potentials. A total of 190 healthy children as controls and 414 patients with CCFS participated in this study. Both patients and controls had (i) event-related potentials (including P300, P100, N150 and P200 measurements); (ii) component analysis of electrocardiographic R-R interval to evaluate autonomic function; and (iii) KANA-Pick-out test to evaluate frontal lobe function. The cutoff threshold defining abnormal P300 latency to target stimuli and amplitude to non-target stimuli was set at two standard deviations above the mean values of controls. Forty patients (classified as Type-I) had an abnormally-prolonged P300 latency to target stimuli, and 49 patients (classified as Type-II) had an abnormally-exaggerated P300 amplitude, and the remaining 325 patients whose P300 latency and amplitude ranged below the above-mentioned threshold were classified as Type-III. All patient groups had normal P100, N150 and P200 measurements. Component analysis of electrocardiographic R-R intervals revealed that the power of high-frequency components was lower in all patient groups, compared to controls. The score in KANA-Pick-out test was worse in all patient groups compared to controls; Type-I Group had the worst score and Type-II Group had the best score among the patients. Taken together, we speculate that abnormally-prolonged P300 latency to target stimuli might be associated with learning disability and abnormally-exaggerated P300 amplitude to non-target stimuli might be associated with hypersensitivity such as phobia in patients with CCFS. Psychosomatic symptoms in patients with CCFS might be associated with higher-order level cognitive dysfunction.
Keywords: Event-related potential; P300; childhood type chronic fatigue syndrome; electrocardiographic R-R interval; frontal lobe function